2010
DOI: 10.1016/j.neuroscience.2010.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic axons from the lateral habenula mainly terminate on GABAergic neurons of the ventral midbrain

Abstract: (deutsch)Einleitung Abstract (English)The concept of cortical-subcortical loops emphasizes the importance of the basal ganglia for motor, psychomotor, and emotional cortical functions. These loops are bidirectionally controlled by the midbrain dopaminergic system, predominantly but not exclusively at the level of the striatum, including the accumbens nucleus. Successful behaviors increase the activities of the mesostriatal (arising in the complex part of the substantia nigra) and mesolimbic (arising in the ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
151
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(168 citation statements)
references
References 62 publications
12
151
0
5
Order By: Relevance
“…These observations are mostly in line with those of previous studies. Thus, the position and density of anterogradely labeled fibers in the VTA proper described here are similar to those described in previous studies examining LHb inputs to the VTA (e.g., Herkenham and Nauta, 1979;Araki et al, 1988;Omelchenko et al, 2009;Brinschwitz et al, 2010). Our observation of many PHA-L-labeled LHb axons in the VTA interpreted as fibers of passage is supported by the findings of recent ultrastructural studies that estimated a much lower synaptic incidence of LHb axons in the VTA (Omelchenko et al, 2009) than in the RMTg (Balcita-Pedicino et al, 2011).…”
Section: Topographical Position Of the Rmtgsupporting
confidence: 90%
See 1 more Smart Citation
“…These observations are mostly in line with those of previous studies. Thus, the position and density of anterogradely labeled fibers in the VTA proper described here are similar to those described in previous studies examining LHb inputs to the VTA (e.g., Herkenham and Nauta, 1979;Araki et al, 1988;Omelchenko et al, 2009;Brinschwitz et al, 2010). Our observation of many PHA-L-labeled LHb axons in the VTA interpreted as fibers of passage is supported by the findings of recent ultrastructural studies that estimated a much lower synaptic incidence of LHb axons in the VTA (Omelchenko et al, 2009) than in the RMTg (Balcita-Pedicino et al, 2011).…”
Section: Topographical Position Of the Rmtgsupporting
confidence: 90%
“…There is now overwhelming evidence that a direct projection from the LHb to the VTA proper is glutamatergic Brinschwitz et al, 2010) and comparatively sparse, forming only a few synapses with no overt selectivity for GABA versus DA neurons (Omelchenko et al, 2009). Altogether, these findings indicate that the LHb may only exert a modest direct influence on VTA neurons, suggesting that the mostly GABAergic RMTg might be a critical relay for LHb inputs to the VTA.…”
mentioning
confidence: 99%
“…Noteworthy, activity of DA and LHb neurons appears to be causally correlated, as electrical stimulation of the LHb inhibits DA neurons (Christoph et al, 1986;Ji and Shepard, 2007;Matsumoto and Hikosaka, 2007). However, the sparse innervation of DA neurons by excitatory LHb afferents (Brinschwitz et al, 2010;Omelchenko et al, 2009) unlikely explains this inhibition, and the presence of an area intermediate between the LHb and the VTA was originally postulated. Elegant studies by Jhou et al (2009a, b) revealed that g-aminobutyric acid (GABA) neurons in the rostromedial tegmental nucleus (RMTg), a region also denominated as 'tail' of the VTA (Perrotti et al, 2005), integrate input from the LHb and send output projection to midbrain DA neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, stimulating LHb neurons will inhibit DA neurons [21]. The inhibition of LHb on DA neurons may arise from the direct projection from LHb neuron to inhibitory interneurons in the VTA/SNc [23] or indirectly through some inhibitory nucleus. In fact, experiments have revealed a path from the LHb to DA neurons through RMTg and neurons in the RMTg seem to encode aversive stimuli [19,20].…”
Section: Lhb Inhibits Snc/vta Via Rmtgmentioning
confidence: 99%